An Outpatient Management Strategy Using a Coronataxi Digital Early Warning System Reduces Coronavirus Disease 2019 Mortality. (8th February 2022) - Lim, Adeline; Hippchen, Theresa; Unger, Inga; Heinze, Oliver; Welker, Andreas; Kräusslich, Hans-Georg; Weigand, Markus A; Merle, Uta
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has caused sudden, severe strain to healthcare systems. Better outpatient management is required to save lives, manage resources effectively, and prepare for future pandemics. Methods: The Coronataxi digital early warning (CDEW) system deployed in Rhein-Neckar County and Heidelberg, Germany is an outpatient care system consisting of remote digital monitoring via a mobile application, a medical doctor dashboard, and medical care delivery to COVID-19 patients in home quarantine when indicated. Patients reported their symptoms, temperature, breathing rate, oxygen saturation, and pulse via the app. This single-center cohort study compared outcomes of the population with and without using the CDEW system. The primary outcome was mortality; the secondary outcomes were hospitalization, duration of hospitalization, intensive care therapy, and mechanical ventilation. Results: Mortality rate was 3- to 4-fold lower and hospitalization rate was higher in the CDEW cohort (459 patients) compared with the cohort without CDEW in the same test area and other regions (Mannheim, Karlsruhe town, Karlsruhe district, and Germany), (mortality rate: 0.65% [95% confidence interval CI, .13%–1.90%] versus 2.16%, 2.32%, 2.48%, 2.82% and 2.76%, respectively, P < .05 for all; hospitalization rate: 14.81% [95% CI, 11.69%–18.40%] versus 6.89%, 6.93%, 6.59%, 6.15%, and 7.22%, respectively, P < .001 for all). The median duration of hospitalization in the CDEW cohort was significantly lower compared with a national sentinel cohort (6 days [interquartile range IQR, 4–9.75 days] versus 10 days [IQR, 5–19 days]; Z = −3.156; P = .002). A total of 1.96% patients needed intensive care and 1.09% were mechanically ventilated. Conclusions: The CDEW system significantly reduced COVID-19 mortality and duration of hospitalization and can be applied to the management of future pandemics. Abstract : This COVID-19 outpatient care system using early remote digital monitoring (symptoms, vital parameter, peripheral oxygen saturation) and home care reduced mortality 3- to 4-fold and increased hospitalization rate with shorter hospital stay, low use of intensive care, and mechanical ventilation.